MANET test-bed implementation and performance analysis - Cai, Ruojun (2011)
Wireless mobile ad hoc network is a infrastructure less network where each node not only acts as a host but also acts as a router. Since the nodes are mobile, the environment is highly dynamic. For these networks to function properly a routing protocol is required that can respond to the rapid changes in the topology. Many routing protocols have been developed for accomplishing this task. Optimized Link State Routing (OLSR) protocol is a well known proactive routing protocol, which is undergoing extensive research under the auspices of the Internet Engineering Task Force (IETF). OLSR can support both static and mobile network configurations and has good scalability properties. The protocol‘s performance in ad-hoc network scenarios has been evaluated with the help of simulations in numerous prior works. However, it has became increasingly apparent that simulations alone are not sufficient to evaluate protocols used in wireless networks. The objective of this project is to evaluated the performance of mobile Ad hoc Networks (MANET) performance by using OLSR routing protocol on an actual wireless test-bed that has been developed using several laptops with LAN card. I developed two basic frameworks which are mobility test bed and bandwidth test bed, since these are two main factors that are particular to MANETs.